A gene-based genetic linkage and comparative map of the rat X chromosome. - Millwood, I; Bihoreau, M; Gauguier, D; Hyne, G; Levy, E; Kreutz, R; Lathrop, G; Monaco, A (1997)
We have constructed a gene-based genetic linkage map of the rat X chromosome. Fifteen polymorphic microsatellite markers associated with 13 different X chromosome genes have been isolated and genotyped on F2 progency from five different intercrosses. These markers have been integrated with 23 further rat X chromosome markers, resulting in a single linkage group for the X chromosome containing 38 microsatellite markers associated with 21 different genes and spanning a genetic distance of 88 cM. Fluorescence in situ hybridization was used to confirm the gene order obtained for the new markers and also placed 2 further genes, Hprt and Fmr1, on the map. Comparisons of gene order among rat, mouse, and human indicate homologous regions of conserved synteny and regions where evolutionary breakpoints have occurred. The genes from human Xq are conserved in order on the rat X chromosome, whereas those from human Xp have been rearranged into at least four conserved segments. The polymorphic markers and comparative map will be useful in studies on rat models of genetic disease.